Dinamika Kehidupan Sosial Masyarakat Pedesaan: Analisis dari Perspektif Sosiologi - Amalia Vidra Tanti; Pambudi Handoyo (Journal on Education, 2025)
This study examines the dynamics of rural social life from a sociological perspective using structural-functional, conflict, and symbolic interactionist theories. The findings reveal that rural communities are characterized by mutual cooperation, dependence on the agrarian sector, and strong social solidarity. However, modernization brings challenges, such as shifts in traditional values and intergenerational conflicts. Structural-functional theory illustrates social stability through mechanisms like mutual cooperation, while conflict theory highlights social change driven by group tensions. The symbolic interactionist perspective explains how individuals create and modify values through daily interactions. This study provides an in-depth understanding of rural social dynamics and serves as a guide for inclusive sustainable development policies in rural communities.